ANALYSIS OF TOTAL QUALITY MANAGEMENT (TQM) BY EMPLOYEES TOWARDS CONSTRUCTIVE IMPROVEMENT EFFORTS IN HOSPITAL - Istahara; Abdul Gani Sidqi; Vip Paramarta; Farida Yuliaty; Kosasih; Fitriana (RADJA PUBLIKA, 2026)
The Emergency Department (ED) is a strategic service unit of hospitals with a high level of complexity and a significant potential for patient complaints if service quality is not optimally managed. Patient complaints not only reflect dissatisfaction but can also be utilized as a constructive effort for service quality improvement. This study aims to analyze the implementation of Total Quality Management (TQM) by employees toward constructive hospital efforts as measured through patient complaints in the Emergency Department of Sultan Imanuddin Regional General Hospital. This study employed a quantitative method with descriptive and verificative approaches. Data were collected through questionnaires distributed to ED staff and supported by patient complaint records, then analyzed using multiple linear regression analysis. The results indicate that both partially and simultaneously, TQM dimensions including customer focus, leadership, continuous improvement, employee involvement, process approach, and fact-based decision making have a significant effect on constructive hospital efforts. Proper implementation of TQM is proven to reduce the number of complaints and improve the quality of emergency services. This study concludes that consistent implementation of TQM is an important strategy in managing patient complaints as a means of continuous improvement and enhancement of hospital service quality.